Carbon nano-onions (multi-layer fullerenes): chemistry and applications - Bartelmess, Juergen; Giordani, Silvia (Beilstein Journal of Nanotechnology, 2014)
This review focuses on the development of multi-layer fullerenes, known as carbon nano-onions (CNOs). First, it briefly summarizes the most important synthetic pathways for their preparation and their properties and it gives the reader an update over new developments in the recent years. This is followed by a discussion of the published synthetic procedures for CNO functionalization, which are of major importance when elucidating future applications and addressing drawbacks for possible applications, such as poor solubility in common solvents. Finally, it gives an overview over the fields of application, in which CNO materials were successfully implemented.
Keywords: carbon nanomaterials; carbon nano-onions; fullerenes; functionalization

(untitled) - Kroto, H. W.; Heath, J. R.; O’Brien, S. C.; Curl, R. F.; Smalley, R. E. (Nature, 1985)

(untitled) - Bollmann, W.; Spreadborough, J. (Nature, 1960)

(untitled) - Iijima, S. (Nature, 1991)

(untitled) - Iijima, S.; Ichihashi, T. (Nature, 1993)

(untitled) - Iijima, S.; Yudasaka, M.; Yamada, R.; Bandow, S.; Suenaga, K.; Kokai, F.; Takahashi, K. (Chem. Phys. Lett., 1999)

(untitled) - Danilenko, V. V. (Phys. Solid State, 2004)

(untitled) - Novoselov, K. S.; Geim, A. K.; Morozov, S. V.; Jiang, D.; Zhang, Y.; Grigorieva, I. V.; Firsov, A. A. (Science, 2004)

(untitled) - Ugarte, D. (Nature, 1992)

(untitled) - Kuznetsov, V. L.; Chuvilin, A. L.; Moroz, E. M.; Kolomiichuk, V. N.; Shaikhudtdinov, S. K.; Butenko, Y. V.; Mal’kov, I. Y. (Carbon, 1994)

Chemistry of Nanocarbons - Echegoyen, L.; Ortiz, A.; Chaur, M. N.; Palkar, A. J. (Carbon Nano Onions, 2010)

(untitled) - Kuznetsov, V. L.; Chuvilin, A. L.; Butenko, Y. V.; Mal’kov, I. Y.; Titov, V. M. (Chem. Phys. Lett., 1994)

(untitled) - Tomita, S.; Sakurai, T.; Ohta, H.; Fujii, M.; Hayashi, S. (J. Chem. Phys., 2001)

(untitled) - Qin, L.-C.; Iijima, S. (Chem. Phys. Lett., 1996)

(untitled) - Sano, N.; Wang, H.; Chhowalla, M.; Alexandrou, I.; Amaratunga, G. A. J. (Nature, 2001)

(untitled) - Alexandrou, I.; Wang, H.; Sano, N.; Amaratunga, G. A. J. (J. Chem. Phys., 2004)

(untitled) - Han, F.-D.; Yao, B.; Bai, Y.-J. (J. Phys. Chem. C, 2011)

(untitled) - Ghosh, M.; Sonkar, S. K.; Saxena, M.; Sarkar, S. (Small, 2011)

(untitled) - Choucair, M.; Stride, J. A. (Carbon, 2012)

(untitled) - Ugarte, D. (Carbon, 1995)

(untitled) - Roy, D.; Chhowalla, M.; Wang, H.; Sano, N.; Alexandrou, I.; Clyne, T. W.; Amaratunga, G. A. J. (Chem. Phys. Lett., 2003)

(untitled) - Krishnamurthy, S.; Butenko, Y. V.; Dhanak, V. R.; Hunt, M. R. C.; Šiller, L. (Carbon, 2013)

(untitled) - Singh, P.; Campidelli, S.; Giordani, S.; Bonifazi, D.; Bianco, A.; Prato, M. (Chem. Soc. Rev., 2009)

Carbon Nanotubes and Related Structures: Synthesis, Characterization, Functionalization, and Applications - Herranz, M. A.; Martin, N. (Noncovalent Functionalization of Carbon Nanotubes, 2010)

Carbon Nanotubes and Related Structures: Synthesis, Characterization, Functionalization, and Applications - Hauke, F.; Hirsch, A. (Covalent Functionalization of Carbon Nanotubes, 2010)

(untitled) - Georgakilas, N.; Guldi, D. M.; Signorini, R.; Bozio, R.; Prato, M. (J. Am. Chem. Soc., 2003)

(untitled) - Rettenbacher, A. S.; Elliott, B.; Hudson, J. S.; Amirkhanian, A.; Echegoyen, L. (Chem. – Eur. J., 2006)

(untitled) - Palkar, A.; Melin, F.; Cardona, C. M.; Elliott, B.; Naskar, A. K.; Edie, D. D.; Kumbhar, A.; Echegoyen, L. (Chem. – Asian J., 2007)

(untitled) - Liu, Y.; Vander Wal, R. L.; Khabashesku, V. N. (Chem. Mater., 2007)

(untitled) - Kuznetsov, O. V.; Pulikkathara, M. X.; Lobo, R. F. M.; Khabashesku, V. N. (Russ. Chem. Bull., 2010)

(untitled) - Rettenbacher, A. S.; Perpall, M. W.; Echegoyen, L.; Hudson, J.; Smith, D. W., Jr (Chem. Mater., 2007)

(untitled) - Bergman, R. G. (Acc. Chem. Res., 1973)

(untitled) - Palkar, A.; Kumbhar, A.; Athans, A. J.; Echegoyen, L. (Chem. Mater., 2008)

(untitled) - Zhou, L.; Gao, C.; Zhu, D.; Xu, W.; Chen, F. F.; Palkar, A.; Echegoyen, L.; Kong, E. S.-W. (Chem. – Eur. J., 2009)

(untitled) - Cioffi, C. T.; Palkar, A.; Melin, F.; Kumbhar, A.; Echegoyen, L.; Melle-Franco, M.; Zerbetto, F.; Rahman, G. M. A.; Ehli, C.; Sgobba, V.; Guldi, D. M.; Prato, M. (Chem. – Eur. J., 2009)

(untitled) - Kordatos, K.; Da Ros, T.; Bosi, S.; Vázquez, E.; Bergamin, M.; Cusan, C.; Pellarini, F.; Tomberli, V.; Baiti, B.; Pantarotte, D.; Georgakilas, V.; Spalluto, G.; et al. (J. Org. Chem., 2001)

(untitled) - Luszczyn, J.; Plonska-Brzezinska, M. E.; Palkar, A.; Dubis, A. T.; Simionescu, A.; Simionescu, D. T.; Kalska-Szostko, B.; Winkler, K.; Echegoyen, L. (Chem. – Eur. J., 2010)

(untitled) - Flavin, K.; Chaur, M. N.; Echegoyen, L.; Giordani, S. (Org. Lett., 2010)

(untitled) - Bahr, J. L.; Yang, J.; Kosynkin, D. V.; Bronikowski, M. J.; Smalley, R. E.; Tour, J. M. (J. Am. Chem. Soc., 2001)

(untitled) - Yang, M.; Flavin, K.; Kopf, I.; Radics, G.; Hearnden, C. H. A.; McManus, G. J.; Moran, B.; Villalta-Cerdas, A.; Echegoyen, L. A.; Giordani, S.; Lavelle, E. C. (Small, 2013)

(untitled) - Giordani, S.; Bartelmess, J.; Frasconi, M.; Biondi, I.; Cheung, S.; Grossi, M.; Wu, D.; Echegoyen, L.; O’Shea, D. F. (J. Mater. Chem. B, 2014)

(untitled) - Bartelmess, J.; De Luca, E.; Signorelli, A.; Baldrighi, M.; Becce, M.; Brescia, R.; Nardone, V.; Parisini, E.; Echegoyen, L.; Pompa, P. P.; Giordani, S. (Nanoscale, 2014)

(untitled) - Molina-Ontaria, A.; Chaur, M. N.; Plonska-Brzezinska, M. E.; Echegoyen, L. (Chem. Commun., 2013)

(untitled) - Breczko, J.; Winkler, K.; Plonska-Brzezinska, M. E.; Villalta-Cerdas, A.; Echegoyen, L. (J. Mater. Chem., 2010)

(untitled) - Breczko, J.; Plonska-Brzezinska, M. E.; Echegoyen, L. (Electrochim. Acta, 2012)

(untitled) - Plonska-Brzezinska, M. E.; Mazurczyk, J.; Palys, B.; Breczko, J.; Lapinski, A.; Dubis, A. T.; Echegoyen, L. (Chem. – Eur. J., 2012)

(untitled) - Plonska-Brzezinska, M. E.; Breczko, J.; Palys, B.; Echegoyen, L. (ChemPhysChem, 2013)

(untitled) - Plonska-Brzezinska, M. E.; Lewandowski, M.; Blaszyk, M.; Molina-Ontario, A.; Luciński, T.; Echegoyen, L. (ChemPhysChem, 2012)

(untitled) - Plonska-Brzezinska, M. E.; Brus, D. M.; Breczko, J.; Echegoyen, L. (Chem. – Eur. J., 2013)

(untitled) - Lei, H.; Luo, J.; Tong, L.; Peng, L.-q.; Qi, Y.; Jia, Z.-g.; Wei, Q. (Food Chem., 2011)

(untitled) - Ding, L.; Stilwell, J.; Zhang, T.; Elboudwarej, O.; Jiang, H.; Selegue, J. P.; Cooke, P. A.; Gray, J. W.; Chen, F. F. (Nano Lett., 2005)

(untitled) - Sonkar, S. K.; Ghosh, M.; Roy, M.; Begum, A.; Sarkar, S. (Mater. Express, 2012)

(untitled) - Gong, H.; Peng, R.; Liu, Z. (Adv. Drug Delivery Rev., 2013)

(untitled) - Shen, J.; Zhu, Y.; Yang, X.; Li, C. (Chem. Commun., 2012)

(untitled) - Seymour, M. B.; Su, C.; Gao, Y.; Lu, Y.; Li, Y. (J. Nanopart. Res., 2012)

(untitled) - Portet, C.; Yushin, G.; Gogotsi, Y. (Carbon, 2007)

(untitled) - Bushueva, E. G.; Galkin, P. S.; Okotrub, A. V.; Bulusheva, L. G.; Gavrilov, N. N.; Kuznetsov, V. L.; Moiseekov, S. I. (Phys. Status Solidi B, 2008)

(untitled) - Pech, D.; Brunet, M.; Durou, H.; Huang, P.; Mochalin, V.; Gogotsi, Y.; Taberna, T.-L.; Simon, P. (Nat. Nanotechnol., 2010)

(untitled) - McDonough, J. K.; Frolov, A. I.; Presser, V.; Niu, J.; Miller, C. H.; Ubieto, T.; Fedorov, M. V.; Gogotsi, Y. (Carbon, 2012)

(untitled) - Borgohain, R.; Li, J.; Selegue, J. P.; Cheng, Y.-T. (J. Phys. Chem. C, 2012)

(untitled) - Gao, Y.; Zhou, Y. S.; Qian, M.; He, X. N.; Redepenning, J.; Goodman, P.; Li, H. M.; Jiang, L.; Lu, Y. F. (Carbon, 2013)

(untitled) - Plonska-Brzezinska, M. E.; Brus, D. M.; Molina-Ontaria, A.; Echegoyen, L. (RSC Adv., 2013)

(untitled) - Wang, Y.; Yu, S. F.; Sun, C. Y.; Zhu, T. J.; Yang, H. Y. (J. Mater. Chem., 2012)

(untitled) - Landi, B. J.; Ganter, M. J.; Cress, C. D.; DiLeo, R. A.; Raffaelle, R. P. (Energy Environ. Sci., 2009)

(untitled) - Wang, Y.; Yan, F.; Liu, S. W.; Tan, A. Y. S.; Song, H.; Sun, X. W.; Yang, H. Y. (J. Mater. Chem. A, 2013)

(untitled) - Wang, Y.; Han, Z. J.; Yu, S. F.; Song, R. R.; Song, H. H.; Ostrikov, K.; Yang, H. Y. (Carbon, 2013)

(untitled) - Xu, B.; Yang, X.; Wang, X.; Guo, J.; Liu, X. (J. Power Sources, 2006)

(untitled) - Liu, L.; Das, A.; Megaridis, C. M. (Carbon, 2014)

(untitled) - Shenderova, O.; Tyler, T.; Cunningham, G.; Ray, M.; Walsh, J.; Casulli, M.; Hens, S.; McGuire, G.; Kuznetsov, V.; Lipa, S. (Diamond Relat. Mater., 2007)

(untitled) - Maksimenko, S. A.; Rodionova, V. N.; Slepyan, G. Y.; Karpovich, V. A.; Shenderova, O.; Walsh, J.; Kuznetsov, V. L.; Mazov, I. N.; Moseenkov, S. I.; Okotrub, A. V.; Lambin, P. (Diamond Relat. Mater., 2007)

(untitled) - Shenderova, O.; Grishko, V.; Cunningham, G.; Moseekov, S.; McGuire, G.; Kuznetsov, V. (Diamond Relat. Mater., 2008)

(untitled) - Macutkevic, J.; Adomavicius, R.; Krotkus, A.; Seliuta, D.; Valusis, G.; Maksimenko, S.; Kuzhir, P.; Batrakov, K.; Kuznetsov, V.; Moseenkov, S.; Shenderova, O.; Okotrub, A. V.; et al. (Diamond Relat. Mater., 2008)

(untitled) - Keller, N.; Maksimova, N. I.; Roddatis, V. V.; Schur, M.; Mestl, G.; Butenko, Y. V.; Kuznetsov, V. L.; Schlögl, R. (Angew. Chem., Int. Ed., 2002)

(untitled) - Su, D.; Maksimova, N. I.; Mestl, G.; Kuznetsov, V. L.; Keller, V.; Schlögl, R.; Keller, N. (Carbon, 2007)

(untitled) - Cabioc’h, T.; Thune, E.; Rivière, J. P.; Camelio, S.; Girard, J. C.; Guérin, P.; Jaouen, M.; Henrard, L.; Lambin, P. (J. Appl. Phys., 2002)

(untitled) - Hirata, A.; Igarashi, M.; Kaito, T. (Tribol. Int., 2004)

(untitled) - Street, K. W.; Marchetti, M.; Vander Wal, R. L.; Tomasek, A. J. (Tribol. Lett., 2004)

(untitled) - Matsumoto, N.; Joly-Pottuz, L.; Kinoshita, H.; Ohmae, N. (Diamond Relat. Mater., 2007)

(untitled) - Joly-Pottuz, L.; Vacher, B.; Ohmae, N.; Martin, J. M.; Epicier, T. (Tribol. Lett., 2008)

(untitled) - Yao, Y.; Wang, X.; Guo, J.; Yang, X.; Xu, B. (Mater. Lett., 2008)

(untitled) - Joly-Pottuz, L.; Matsumoto, N.; Kinoshita, H.; Vacher, B.; Belin, M.; Montagnac, G.; Martin, J. M.; Ohmae, N. (Tribol. Int., 2008)

(untitled) - Joly-Pottuz, L.; Bucholz, E. W.; Matsumoto, N.; Phillpot, S. R.; Sinnott, S. B.; Ohmae, N.; Martin, J. M. (Tribol. Lett., 2010)

(untitled) - Koudoumas, E.; Kokkinaki, O.; Konstantaki, M.; Couris, S.; Korovin, S.; Detkov, P.; Kuznetsov, V.; Pimenov, S.; Pustovoi, V. (Chem. Phys. Lett., 2002)

(untitled) - Sek, S.; Breczko, J.; Plonska-Brzezinska, M. E.; Wilczewska, A. Z.; Echegoyen, L. (ChemPhysChem, 2013)